The Effect of the Burnishing Process on the Strain Rate and State Stress in Hollow Steel Tubes - Tomasz Cyryl Dyl; Wioletta Kuśmierska-Matyszczak (Metals)
In this paper, we propose the use of burnishing internal cylindrical surfaces with a hard tool in a mandrel shape. The burnishing force is exerted mainly by the press slide, which has pushing properties, moving the burnisher through the hollow tube. The burnishing of hollow surfaces is used as the finishing step for elements such as tubes. The purpose of using the burnishing method may be, for example, to increase the smoothness and accuracy of the object, for the improvement of its functional and operational properties, for economic reasons, or to increase its resistance to corrosion and fatigue. The depth of plastic deformation and the accuracy of processing are the main differences in the machining effects for individual burnishing methods. The selection of the burnishing conditions depends on the method of exerting pressure from the burnishing elements on the machined surface, which can be elastic or rigid. Computer simulations of the burnishing process were performed in FORGE® NxT 2.1 software. A numerical analysis was performed using a three-dimensional triangular mesh. The theoretical and experimental research was determined to have very good compatibility, as determined by the numerically calculated results and by the mean deviation of residual stress method. This research analyzed the stress and strain state after the burnishing process, and a depth of deformation of approximately 20 μm to 30 μm in the material was determined.